Realistic Parallel Programming Productivity: Authors’ Response. - Richards, John T.; Brezin, Jonathan; Swart, Calvin B.; Halverson, Christine A. (Communications of the ACM, 2015)
The article presents a response from John T. Richards, Jonathan Brezin, Calvin B. Swart, and Christine A. Halverson to issues raised in a reader's letter concerning their article "A Decade of Progress in Parallel Programming Productivity" which appeared in the November 2014 issue.